Bounded Solidarity as an Asset for Public Health Care Intervention. (February 2022) - Yter, Mireia; Murillo, David; Georgiou, Andreas
The relationship between social capital and public health has been extensively analyzed. However, not much has been written about the formation of social capital among citizens and public health workers in times of a pandemic. Our aim is to analyze social capital development through the prism of bounded solidarity and seek its manifestations toward public health workers. A qualitative self-administered survey was used to analyze what actions, practices, attitudes, and reasons inspired citizens to behave as they did with respect to public health workers during the first weeks of lockdown under the COVID-19 pandemic. Respondents, mostly from European countries, reveal that citizens aimed to prevent the collapse of the public health system through reinforcing trust toward institutions, legitimizing health care personnel expertise, practicing reciprocity and altruism, giving recognition to public health workers, and providing them with means. Finally, recommendations for public health communication on risks and crises are discussed.